Political topology of Europe - Rosicki, Remigiusz (Wydawnictwo Naukowe WNPiD UAM, 2019)
The objective scope of the analysis performed in the text encompasses selected aspects of policy in its topological dimension. The space of policy is understood as both a theoretical construct (a policy field) and relations between the characteristics of political actors and their special kind of geographical co-existence. The following have been recognised as essential characteristics of policymaking: (1) electoral process and pluralism, (2) functioning of government, (3) political participation, (4) political culture and (5) civil liberties. These features can become an object of analysis in the assessment of democratic and authoritarian tendencies in selected countries. The text uses two statistical methods of multidimensional comparative analysis (Ward’s method and k-means method), apart from which use has been made of basic descriptive statistics and a comparative analysis of the values of the parameters of political characteristics. A selection of 40 European countries (EU-28 and 12 other countries) have been subjected to a statistical analysis according to the 2018 data. The main goal of the analysis is to connect facts and characteristics attributed to policy with a specific geographical area. In order to elaborate the objective scope of the research problem, the following research questions have been presented in the text: (1) Which of the characteristics of policy will determine the division of state entities according to a special type of clusters?, (2) Will political characteristics determine the division of particular state entities according to a special type of geographical division? The addressed research questions have been related to the hypotheses subjected to verification in the text.

Zakres przedmiotowy analizy w tekście obejmuje wybrane aspekty polityki w jej wymiarze topologicznym. Przestrzeń polityki rozumie się zarówno jako konstrukt teoretyczny (pole polityki), ale i jako zależności między cechami podmiotów politycznych i ich szczególnym rodzajem współwystępowania geograficznego. Za istotne cechy polityki uznano: (1) proces wyborczy i pluralizm, (2) funkcjonowanie administracji publicznej, (3) partycypację polityczną, (4) kulturę polityczną i (5) swobody obywatelskie. Cechy te stanowić też mogą przedmiot oceny tendencji demokratycznych i autorytarnych w wybranych państwach. W tekście wykorzystano dwie statystyczne metody wielowymiarowej analizy porównawczej (metodę Warda i k-średnich), obok nich wykorzystano też podstawowe statystyki opisowe oraz analizę porównawczą wartości parametrów cech polityki. Analizie statystycznej poddano czterdzieści wybranych państw europejskich (UE-28 i 12 pozostałych) wedle danych na 2018 rok. Głównym celem analizy jest powiązanie faktów i cech przypisanych polityce z określonym obszarem geograficznym. W celu uszczegółowienia zakresu przedmiotowego problemu badawczego w tekście przedstawiono następujące pytania badawcze: (1) Które z cech polityki decydować będą o podziale podmiotów państwowych wedle szczególnego rodzaju grup?, (2) Czy cechy polityczne decydować będą o podziale poszczególnych podmiotów państwowych wedle szczególnego rodzaju podziału geograficznego? Wskazane pytania badawcze związano odpowiednio z hipotezami, które są przedmiotem weryfikacji w tekście.
Topologia polityczna Europy
Keywords: theory of policymaking; topology of policymaking; policy field; political systems; policy diffusion; politics; teoria polityki; topologia polityki; pole polityki; systemy polityczne; dyfuzja polityki; polityka